Protective effects of the dipeptidyl peptidase IV inhibitor sitagliptin in the kidney in a T2DM animal model – Focus on endoplasmic reticulum stress - Marques, Catarina Isabel Rodrigues (2013)
Dissertação de mestrado em Bioquímica apresentada ao Departamento Ciências da Vida da Faculdade de Ciências e Tecnologia da Universidade de Coimbra.